Nomenklatorische Revision der illyrischen Buchenwalder (Verband Aremonio-Fagion) - Mucina, Ladislav; Marincek, L.; Zupancic, M.; Poldini, L.; Dagskobler, I.; Accetto, M. (1993)
A nomenclatural revision of the Illyrian beechwoods of Slovenia, Croatia, southwestern Hungary, southern part of Carinthia (Austria) and northeastern part of Italy (Veneto and Friuli Venezia-Giulia) is presented. Some beechwoods from Bosnia and Herzegovina as well as Montenegro have also been considered. The names of the Aremonio-Fagion, 4 suballiances as well as 22 associations have been revised, nomenclatural types selected and copious synonyma assigned.